2017
DOI: 10.1111/dmcn.13501
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation of the ankle dorsiflexors during walking in spastic cerebral palsy: a systematic review

Abstract: Effects of functional electrical stimulation (FES) point towards a potential role as an alternative to orthoses for patients with spastic cerebral palsy (CP). Some evidence for a decrease in self-reported frequency of toe-drag and falls with the use of FES in spastic CP. Limited evidence for improvements in activity and participation in patients with spastic CP using FES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
(224 reference statements)
0
30
0
4
Order By: Relevance
“…These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93]. Also, taping is better tolerated than traditional orthotics with children often reporting discomfort and dissatisfaction with these interventions or disliking the cosmetic effect [73,140].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93]. Also, taping is better tolerated than traditional orthotics with children often reporting discomfort and dissatisfaction with these interventions or disliking the cosmetic effect [73,140].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…This shift in NMES research toward a focused attention on single-channel stimulation of the tibialis anterior to augment dorsiflexion brought both benefits and potential missed opportunities. Such ubiquitous attention has allowed for the first credible systematic review to be attempted in the field (8). With a review question limited to the effect of functional electrical stimulation during walking on ankle dorsiflexors in children with CP, the reviewers concluded that improvements in active ankle dorsiflexion range of motion, strength, selective motor control, balance and gait kinematics could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the tibialis anterior and augmentation of ankle DF is likely to be a critical component of such future systems; however, it appears unlikely that it alone will resolve gait deficits seen in this population. Interestingly, gait-specific NMES applied to the tibialis anterior was shown to only improve ankle kinematics (8), while the singular recent case study on gait-specific NMES applied to the quadriceps femoris showed only improvements in knee joint kinematics (28). This taken in conjunction with the findings of earlier studies that multi-channel stimulation can have additive beneficial effects, would suggest that normalization of more involved gait deficits, would require a multi-channel gait-specific NMES acting across multiple joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging assistive exercise modes such as functional electrical stimulation show promise for improving muscular strength and function in individuals whose impairments may limit their ability to perform volitional exercise at intensities required to stimulate neuromuscular adaptation. 200 There were some minor variations to the original published protocol (Chapter 3) compared to the version included in this thesis. The original protocol was broad ranging and included all proposed outcome measures at the time of study design.…”
Section: Practical Recommendationsmentioning
confidence: 99%